Evaluasi Karakter Pertumbuhan dan Inflorescence Plasma Nutfah Kapas Introduksi dan Lokal pada Iklim Tropis - Jakty Kusuma (Politeknik Negeri Lampung., 2016)
In order to support the needs of the national textile industry, the necessary raw materials of high quality cotton, high grain yield and widely adaptable. To achieve these objectives, it is necessary the introduction of new cotton crop accession so that the resources can be available breeding elders. Given the genetic diversity and varieties of national cotton production stagnant. The study was conducted with the aim of getting the results of evaluation of growth of cotton plants introduced in tropical environments. Based on the analysis of variance, character growth, plant height, number of branches and monopodial simpodial, and time of harvest showed significant differences in the level of 1%. While the character of days to flowering and boll opening age showed significant differences in the level of 5%. There was variation in plant height were heterogeneous due to genetic differences. Differences in flowering dates, age boll opening and harvesting with significant variation is caused by environmental influences. Anticipated environmental factors that have the most primary role is long irradiation, recorded some sensitivity to fotoperiodisitas accession. The results of the study recommend accession CRIS-664 and CRIS-342 as source code elders with early maturity, because it has a lifespan of flowering and harvesting age equal even faster than local cultivars. Key words: cotton, germplasm, introduction, inflorescence